Insurance payment guarantee fund as a factor of stabilization of the insurance market in the Republic of Kazakhstan - Vorobyova , S.M. (BUKETOV BUSINESS REVIEW, 2019)
Creating of an effective mechanism to protect consumers of insurance services is a relevant issue for Kazakhstan. In the country a system for guaranteeing the obligations of insurance organizations to their insurers in the event of the forced liquidation of insurers — participants of the Insurance Benefit Guarantee Fund has been created. Insurance coverage is guaranteed only for a limited range of types of compulsory insurance, which puts participants in the insurance market in an unequal position. The author of this article defends the point of view that with such an approach to the formation and use of the Insurance Indemnity Guarantee Fund, the main theoretical interdependencies of the insurance business are not taken into account. In particular, the main condition for the effective formation of an insurance fund has been violated, which implies that as many objects as possible, which are not exposed to identical risks, should be included in the range of insurance relations. This theoretical position suggests that the Insurance Indemnity Guarantee Fund should become universal and provide insurance coverage for all types of general insurance, both compulsory and voluntary. Voluntary life insurance contracts are not included in the scope of the Fund’s liability. But at the same time, in the event of the forced liquidation of insurance organizations in this industry, the property interests of each policyholder are already affected and the amount of guarantee insurance payments will be disproportionately larger than under general insurance contracts. Therefore, the creation of a guarantee mechanism for savings insurance contracts is considered a priority task of the national system of guaranteeing insurance payments.